Effect of dietary calcium on the colonic luminal environment. Issue 11 (November 1991) - Appleton, G V; Owen, R W; Wheeler, E E; Challacombe, D N; Williamson, R C
Abstract : Dietary supplementation with calcium may prevent the development of colorectal cancer. This mechanism may be related to fatty acid and bile salt chelation in the small bowel forming non-toxic calcium-soap compounds. Calcium may also act locally or systemically on the colonic mucosa. Faecal concentrations of free fatty acids and free bile acids were measured in 17 Sprague-Dawley rats (weighing 472 (39 g)) whose daily calcium intake had been trebled by enriching the chow and adding calcium lactate (24 g/l) to the drinking water. Mean (SEM) faecal concentrations of free bile acids were 33% less than in 19 controls (1.23 (0.15) v 1.82 (0.20) mg/g; p less than 0.001), whereas free fatty acid concentrations were 117% higher (14.68 (3.59) v 6.76 (2.41) mg/g; p less than 0.02). The 'direct' effect of calcium was assessed by organ culture of rat colonic explants in three different concentrations of calcium. Crypt cell production rate (measured by a stathmokinetic technique), which was (mean (SEM)) 4.80 (0.23) cells/crypt/h in control medium (Ca2+ = 2.14 mmol/l), fell by 43% when calcium concentration was doubled (p less than 0.05) and by a further 43% when the concentration was trebled (p less than 0.02). Calcium binds free fatty acids but not free bile acids intraluminally. Calcium has a direct antitropic action on colonic crypts.